2023
DOI: 10.1038/s41467-023-36837-x
|View full text |Cite
|
Sign up to set email alerts
|

Retinol dehydrogenase 10 reduction mediated retinol metabolism disorder promotes diabetic cardiomyopathy in male mice

Abstract: Diabetic cardiomyopathy is a primary myocardial injury induced by diabetes with complex pathogenesis. In this study, we identify disordered cardiac retinol metabolism in type 2 diabetic male mice and patients characterized by retinol overload, all-trans retinoic acid deficiency. By supplementing type 2 diabetic male mice with retinol or all-trans retinoic acid, we demonstrate that both cardiac retinol overload and all-trans retinoic acid deficiency promote diabetic cardiomyopathy. Mechanistically, by construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For studies on the risk of diabetic complications from retinol, Zhang C et al showed that a higher dietary intake of retinol or retinol equivalents was associated with a lower risk of diabetic retinopathy, per 100 μg/day higher in dietary retinol equivalent intake was associated with 12% lower risk of diabetic retinopathy 17 . Retinol dehydrogenase-10 reduction-mediated disruption of retinol metabolism was found to promote diabetic myocardial ferroptosis in male mice, but this occurrence was ameliorated by retinol supplementation 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For studies on the risk of diabetic complications from retinol, Zhang C et al showed that a higher dietary intake of retinol or retinol equivalents was associated with a lower risk of diabetic retinopathy, per 100 μg/day higher in dietary retinol equivalent intake was associated with 12% lower risk of diabetic retinopathy 17 . Retinol dehydrogenase-10 reduction-mediated disruption of retinol metabolism was found to promote diabetic myocardial ferroptosis in male mice, but this occurrence was ameliorated by retinol supplementation 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A negative association was observed between higher dietary retinol or retinol equivalent intake and the risk of diabetic retinopathy, with each 100 μg/d increase in dietary retinol equivalent associated with a 12% reduction in risk 17 . Retinol metabolism disorder was involved in the development of myocardial injury in T2DM and the injury was improved with retinol intake 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar protective medicines, such as retinoic acid, may regulate ferroptosis to reduce damage to the ICM. However, their pharmacological mechanisms have not yet been explored ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Retinol dehydrogenase 10 (RDH10) metabolism disorder exists in the hearts of mice and the patients with type 2 diabetes mellitus (T2DM) ( 96 ). Reduction in RDH10 inhibits GPX4 and FSP1, promoting ferroptosis ( 97 ). In the model of T2D mice with DCM, sulforaphane (a Nrf2 activator) ameliorates cardiac ferroptosis in AMPK/Nrf2-dependent way ( 98 ).…”
Section: Ferroptosis and Cvdsmentioning
confidence: 99%